Prioritization of Research Vessel Lubricating Oil System Equipment for Maintenance Purpose Using Failure Mode Effect and Criticality Analysis (FMECA) Method. Study Case: RV. Baruna Jaya - Tris Handoyo; Dhimas Widhi Handani; Agus Sudaryanto; Dimas Fajar Prasetyo (Department of Naval Architecture - Diponegoro University, 2023)
Alongside the program, which requires research vessel operation, RV Baruna Jaya is needed to fill that requirement fully. RV Baruna Jaya reported many failures during the previous mission. Some failures need emergency maintenance. One of them is the problem with the lubricating oil system. The lubrication system of an engine supplies of lubricating oil to the various moving parts of the engine. Its main function is to form an oil film between moving parts, which reduces friction and wear. The lubricating oil is also used as a cleaner and, in some engines, as a coolant. During the survey Ina-TEWS in 2021, RV Baruna Jaya was ordered due high temperature of The Lubricating Oil System. The temperature exceeded the normal value, and due to safety considerations, the ME needed to be shut down. Because of this problem, the survey carried out by RV Baruna Jaya was delayed. So, it is important to maintain a lubricating oil system. In this analysis, to maintain the function and performance of the lubricating oil system, the FMECA is carried out. By prioritizing the lubricating oil system equipment using FMEA and Criticality Analysis, 6 pieces of equipment with 24 failure modes should be maintained. These equipment are lubricating oil cooler, lubricating oil pump, engine service oil tank, engine reserve oil tank, Engine lubricating oil standby pump, and lubricating oil transfer pump. The maintenance task is proposed to minimize the occurrence of failure mode, which could possibly happen in the equipment.